Formulation of novel polymer coated iron oxide nanoparticles - Abushrida, Ahmed (2012)
The aim of this study was to investigate how to produce iron oxide nanoparticles, with the potential for long circulation times or the ability to preferentially reach particular tissues. The preparation of iron oxide nanoparticles was achieved using inorganic solution methods to prepare particles of small size using a narrow size distribution. The nanoparticles were coated with dextran and carboxymethyl dextran as reference materials using the same method as in the preparation of the iron oxide nanoparticles. This project investigated the use of the biodegradable polymer poly(glycerol adipate) (PGA) as a coating for iron oxide nanoparticles. PGA is already used in drug delivery systems and showed an ability to control the rate of release of the drug. PGA can be readily modified with pendant functional groups leading to modifications of the physicochemical properties of the polymer. It can also be readily modified to form copolymers with the hydrophilic polymer poly(ethylene glycol) (PEG). PGA 40% acylated with stearic acid (PGA 40%C18) and the PEGylated copolymer PEG–PGA 40%C18 were synthesised for this work. The formulation of coated iron oxide nanoparticles was investigated using PGA and modified PGA polymers. The coating process was optimised producing small coated nanoparticles were measured by TEM and the best sizes are (16 ± 5 nm with PGA while with, modified PGA is 23 ±7 nm and with PEG–PGA 40%C18 is 16 ± 4 in diameter). The PGA–IONPs were over-coated by incubation with albumin and Tween. The coated particles were characterised by DLS, zeta potential, and transmission electron microscopy. The colloidal stability of the various particle formulations was investigated using increasing salt concentrations. These demonstrated that PGA–coated nanoparticles were more stable than the existing dextran formulations, and that increased stability was obtained by overcoating with albumin or Tween. A further increase in stability was seen with PEG-PGA coated nanoparticles. The cellular uptake of the RBITC labelled nanoparticle formulations was studied on the C6 medulloblastoma cell line using monolayer and 3-D aggregate cultures using fluorescence microscopy, confocal microscopy, transmission electron microscopy (TEM) and flow cytometry. The results indicated that these particles were readily internalised in C6 cells, but with an unusual subcellular distribution. Uptake was dependent on both nanoparticle concentration and incubation time. The incubation of cells with internalised particles demonstrated that particles were metabolised and fluorescence was lost from cells over a period of 4–12 hours. TEM studies showed that, after 1 hour, nanoparticles were found in all subcellular compartments, but that the route of entry into cells could not be readily determined. Experiments using 3-D cell cultures demonstrated that nanoparticles were readily taken up into aggregates, with nanoparticles penetrating deep into the aggregates. Overall, these studies demonstrated novel formulations of iron oxide nanoparticles coated with well-defined biodegradable PGA polymer layers, which were stable against aggregation under physiological conditions. These formulations show promise for use in a variety of medical applications.